DESAIN ALAT BANTU KONFIGURASI ROUTER BERBASIS GUI (CISCO ROUTER DICTIONARY)) - Kartikadarma Etika; Ihwati Ummi (Semantik, 2011)
In the development of software engineering, many known modeling languages, which aims for a software to convey information effectively and efficiently. Unified modeling language (UML), one of which perform visual modeling of the depiction of the interaction between elements in the system. UML itself has several methods of visualizing a system. Rational Unified Process (RUP) is an example of UML method. RUP is a method of modeling by applying the phases in its processes, namely inception, Elaboration, construction and transition. The difference with other methods, namely by applying the existing phases, then the modeling will be very structured and very detailed, even to know the stages of change that occurred in the modeling. The results of this research is the creation of a tool that can be used to learn about the router, which is to perform global simulation configuration on the router so that it can reduce the level of syntax errors in the string that will be integrated into certain modes contained in such user CISCO Router mode, privileged mode, global configuration mode (config mode), interface modes, and the show running config.Keywords : GUI, RUP, UML, Java, Router Configuration, Routing